Effects of combined tiotropium/olodaterol on inspiratory capacity and exercise endurance in COPD. Issue 4 (20th April 2017) - O'Donnell, Denis E.; Casaburi, Richard; Frith, Peter; Kirsten, Anne; De Sousa, Dorothy; Hamilton, Alan; Xue, Wenqiong; Maltais, François
Two replicate, double-blind, 6-week, incomplete-crossover studies (MORACTO 1 and 2) assessed the effects of tiotropium/olodaterol on inspiratory capacity and exercise endurance time in patients with moderate to severe chronic obstructive pulmonary disease. For each patient, four of five treatments were administered once daily for 6 weeks, with a 21-day washout between treatments: tiotropium/olodaterol 2.5/5 µg or 5/5 µg, tiotropium 5 µg, olodaterol 5 µg or placebo, all via the Respimat inhaler. Primary outcomes were inspiratory capacity prior to exercise and exercise endurance time during constant work-rate cycle ergometry to symptom limitation at 75% of peak incremental work rate after 6 weeks (2 h post-dose). 295 and 291 patients were treated in MORACTO 1 and 2, respectively. Tiotropium/olodaterol 2.5/5 and 5/5 µg provided significant improvements in inspiratory capacity versus placebo and monotherapies (p<0.0001), and significant improvements in exercise endurance time versus placebo (p<0.0001). Intensity of breathing discomfort was reduced following both doses of tiotropium/olodaterol versus placebo (p<0.0001). Once-daily tiotropium/olodaterol yielded improvements in lung hyperinflation versus placebo and statistically significant improvements versus monotherapies. Tiotropium/olodaterol also showed improvements in dyspnoea and exercise tolerance versus placebo but not consistently versus monotherapies. T/O reduces lung hyperinflation in COPD versus T, O or placebo and increases exercise endurance versus placebo http://ow.ly/ml3G307XW6a